Hubungan Kecerdasan Emosional dengan Tingkat Kecemasan selama Masa Pandemi Covid-19 pada Mahasiswa Program Studi Kedokteran Angkatan 2019 Universitas Tanjungpura - Febrianti, Fatayatun Nur; Yuniarni, Desni; Handini, Mitra (Jurnal Kesehatan Andalas, 2024)
Unexpected changes in various aspects of life during the COVID-19 pandemic have made students more vulnerable to anxiety. Anxiety among students, especially medical students, requires more attention because it might affect their academic performance and professional development. One factor that may affect anxiety is the ability to manage emotions or emotional intelligence. The higher the emotional intelligence, the better the emotion management skill. Objective: To determined the correlation between emotional intelligence and anxiety levels during the COVID-19 pandemic among third-year medical students at Tanjungpura University. Methods: This study was an analytical cross-sectional study. A total of 79 students participated in the study. The emotional intelligence and Beck Anxiety Inventory questionnaires were used to measure emotional intelligence and anxiety levels, respectively. Data were analyzed using the Spearman correlation test. Results: The results of the emotional intelligence correlation test with anxiety on self-awareness variables (p = 0.006; r = -0,307), self-control (p = 0.491; r = -0.079), motivation (p = 0.097; r = -0.188), empathy (p = 0.933; r = -0.010), and social skills (p = 0.579; r = -0.063). Conclusion: There is a statistically significant opposite correlation between emotional intelligence on the self-awareness variable and the level of anxiety during the COVID-19 pandemic among third-year medical students at Tanjungpura University.Keywords: emotional intelligence, anxiety, COVID-19 pandemic, medical students